THE IMPACTS OF REAL ACTION FEATURES IN THE MERDEKA MENGAJAR PLATFORM (PMM): MATHEMATICS TEACHER'S PERSPECTIVE: DAMPAK AKSI NYATA DALAM PLATFORM MERDEKA MENGAJAR (PMM): PERSPEKTIF GURU MATEMATIKA - Fadhil Zil Ikram,; Anaguna, Nursyam; Rosidah, (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
This research is a qualitative study that aims to describe the impact of using the real action feature on the Merdeka Mengajar (PMM) platform from the perspective of mathematics teachers. This research was conducted from August 2023 to September 2023. This research uses data obtained from documents or real action information from 22 mathematics teachers from West Sulawesi and South Sulawesi. Data are obtained from descriptions, reflections, and documents that can be accessed on the Merdeka Mengajar platform, especially in the resource person section in the community feature. The mathematics teachers referred to and selected in this study are teachers who are resource persons for the Merdeka curriculum because they are among the teachers who receive many benefits from using the real action feature in PMM. The data analysis used refers to three steps, namely data condensation, data display, and conclusion making. Based on the research results obtained, the real action feature on the Merdeka Mengajar platform has many positive impacts on mathematics teachers, students, and schools. These impacts include improving teacher competence, making teachers visionary person, making teachers accustomed to reflecting, improving the condition of education units, overcoming misconceptions, improving the quality of teacher learning tools, strengthening the relationship between teachers and students, having a positive impact on students, and deepening or adding new knowledge.